What Employers Really Want When Recruiting Recordkeeping Practitioners: Expectations in the Western Australian State Sector - Pember, Margaret (2005)
This paper reports on the major findings from a survey of an employer group in Western Australia, just one phase of continuing research into the degree of professionalism of the recordkeeping industry. A number of different stakeholder groups with an interest in recordkeeping have been identified and the overall project includes a series of surveys of these different stakeholder groups, as well as a graduate survey and a content analysis of recordkeeping advertisements. This particular research exercise was conducted in the Western Australian State Public sector. Two broad trends are apparent in the responses made by the employers: one business process driven, the other a legislative imperative. The first trend identified is the move away from a narrow focus on the management of paper-based hardcopy records to electronic document management (EDM); the second trend a growing awareness of the need for recordkeeping in government agencies to be compliant with relevant legislation. Employers indicated the need for a range of skilled and experienced practitioners to staff their recordkeeping programs.The research also indicates that those employers in the Western Australian State Public Sector responding to the survey identify two distinct groups of recordkeeping practitioners: professionals and day-to-day operational or processing staff. Those regarded as 'professionals' make up less than 30% of those employed in recordkeeping positions. These professional practitioners are in great demand and employers have significant problems filling higher level positions, thus providing a dynamic career path for skilled, experienced and educated recordkeeping professionals.